COVID-19 Pandemic impacts on construction projects - Ataei, Hossein; Becker, Dan, 1971-; Hellenbrand, Joseph R.; Mehany, Mohammed S. Hashem M.; Mitchell, Thomas E.; Ponte, David M. (American Society of Civil Engineers, 2021)
Sponsored by the Claims Avoidance and Resolution Committee of the Construction Institute of ASCE COVID-19 Pandemic Impacts on Construction Projects provides a concise overview of the immediate response of the construction industry to the challenges created by the worldwide COVID-19 outbreak. Topics include time and schedule impacts on projects, financial impacts on projects, and new and evolving regulations. This book will be of interest to field engineers, project managers, and all those involved with claims and construction management Provided by publisher
Keywords: Construction projects -- Management.; Construction projects -- Safety measures.; COVID-19 Pandemic, 2020- -- Economic aspects.; elektronické knihy; electronic books